PORDA DIY BOXING ATHLETE TRAINING OBSTACLES SURVEY BANTUL DISTRICT - Moh Kholil; Ardhika Falaahudin (Journal Physical Health Recreation (JPHR), 2022)
This study aims to improve the boxing retention of the Bantul District Porda who will compete in the DIY Porda event which will be held in September 2022 in the special area of Yogyakarta. This type of research is a descriptive quantitative research consisting of 2 factors, namely external factors and internal factors. The subject used for data collection in this study was a questionnaire that was submitted to all athletes. Analysis of the data used is descriptive quantitative analysis. The results showed that most of the athlete's training problems that were reviewed from Bantul district came from external factors where the athletes were constrained by their training from their surroundings and lifestyle. Meanwhile, the obstacles in the athlete's training that came from internal factors were relatively few because the boxing athlete from the Bantul district had motivated him to become a professional boxing athlete. Thus it can be said that the athlete's training constraints come from external factors or from the environment and habits.